2011
DOI: 10.5047/eps.2010.12.009
|View full text |Cite
|
Sign up to set email alerts
|

ULF impulsive magnetic response at mid-latitudes to lightning activity

Abstract: Induction magnetometer data from the mid-latitude station Moshiri (geomagnetic latitude 35.6• ) has been examined in search of a transient ULF response to the regional lightning activity. For many events, besides the main impulse produced by the lightning discharge, a secondary impulse delayed about 1 sec was observed. These secondary echo-impulses are probably caused by the partial re ection of wave energy of the initial lightning pulse from the upper boundary of the ionospheric Alfven resonator in the topsid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…There is evidence (e.g. Schekotov et al 2011) that the mechanism of the multi-band spectra formation is not related to the oscillatory response of the IAR, but is caused by the specific impulsive structure of geomagnetic disturbances during the regional lightning activity. In general, it is still uncertain how to discriminate the ULF response to distant thunderstorm centres and regional lightning activity, and what is the relative contribution of those sources to IAR stimulation at mid-latitudes.…”
Section: Ionospheric Alfvénic Resonator and Fast Magnetoacoustic Wavementioning
confidence: 99%
“…There is evidence (e.g. Schekotov et al 2011) that the mechanism of the multi-band spectra formation is not related to the oscillatory response of the IAR, but is caused by the specific impulsive structure of geomagnetic disturbances during the regional lightning activity. In general, it is still uncertain how to discriminate the ULF response to distant thunderstorm centres and regional lightning activity, and what is the relative contribution of those sources to IAR stimulation at mid-latitudes.…”
Section: Ionospheric Alfvénic Resonator and Fast Magnetoacoustic Wavementioning
confidence: 99%
“…6c and 6d) the noise component gave a significant contribution to the formation of the resonant structure in the power spectrum of the magnetic components. These studies were initiated in part by the paper [5] in which the pulse component played a predominant role in the formation of the resonant frequency structure in the power spectrum. It should also be noted that the method we used for processing did not distort, in the cases considered, the main parameters of the spectral structures (frequency scales and boundary frequency) which are determined by the local properties of the ionosphere.…”
Section: Experimental Datamentioning
confidence: 99%
“…The superposition of the initial pulse and echo-pulses is separated by time delay Δτ owing to the Alfvén wave propagation up and down in the ionosphere. Indeed, examination of ULF magnetic response to regional lightning activity showed that the mechanism of multiple spectral peak formation was not related to oscillatory response of the ionosphere but caused by a specific multi-pulse structure of geomagnetic disturbances (Schekotov et al, 2011).…”
Section: Introduction: Ulf Resonators and Waveguides In The Terrestrimentioning
confidence: 99%